2015
DOI: 10.1002/lary.25787
|View full text |Cite
|
Sign up to set email alerts
|

Internal auditory canal meningocele‐perilabyrinthine/translabyrinthine fistula: Case report and imaging

Abstract: The case of a 17-year-old patient with progressive unilateral sensorineural hearing loss and temporal bone malformations concerning for internal auditory canal meningocele with translabyrinthine/perilabyrinthine cerebrospinal fluid fistula is presented with associated computed tomography and magnetic resonance imaging. As the second reported case of an unruptured internal auditory canal meningocele with translabyrinthine/perilabyrinthine fistula, the case presents several clinically relevant points for otologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The most common presenting symptoms of the previously reported cases were meningitis, rhinorrhea and conductive hearing loss due to CSF accumulation in the middle ear. (4)(5)(6). The fallopian tunnel is usually shielded from subarachnoid pressures by a tight arachnoid band at the meatal foramen.…”
Section: Discussionmentioning
confidence: 99%
“…The most common presenting symptoms of the previously reported cases were meningitis, rhinorrhea and conductive hearing loss due to CSF accumulation in the middle ear. (4)(5)(6). The fallopian tunnel is usually shielded from subarachnoid pressures by a tight arachnoid band at the meatal foramen.…”
Section: Discussionmentioning
confidence: 99%
“…Upon review of the literature, we found only one other case of an IAC meningocele; that particular patient presented with progressive left-sided hearing loss as his only symptom [5]. Due to this, surgery was not pursued and the case was presented as a reason not to pursue intervention.…”
Section: Discussionmentioning
confidence: 99%